Disability, development and financial exclusion: a study of the socio-economic barriers to accessing microfinance encountered by people with physical disabilities in Kampala, Uganda - Hewitt, Joseph (2018)
This thesis explores the variety of barriers to accessing microfinance that people with disabilities in Uganda experience. The research is based upon both quantitative and qualitative data collected in the capital Kampala in 2014, and comprises of 223 questionnaires with people who have a permanent physical disability and 26 interviews with representatives of both microfinance institutions and disabled persons organisations in Uganda. Analysis of the quantitative data suggests that people with disabilities are able to access credit from formal financial providers such as commercial banks, microfinance institutions and savings and credit cooperatives, but at lower rates than the national average. Despite dominant narratives of microfinance which promote it as means to reduce financial exclusion, just 5% of the survey sample of people with disabilities had gained access to credit through a microfinance institution. The thesis goes on to examine the multitude of factors which impact the ability of people with disabilities to access such services, including the affordability of credit, the design of financial products, physical accessibility, social discrimination and self-exclusion. It also provides an assessment of the ways in which such barriers may be reduced, for example, through the employment of field agents, greater utilisation of mobile money platforms and the design of specific products targeted at people with disabilities. In addition, the research considers the impact that commercialisation has had on the microfinance sector in Uganda, and in particular the effect a move to a for-profit model has had on the accessibility of microfinance for people with disabilities. The thesis concludes by offering specific recommendations to reduce barriers to access, including collecting increased levels of data on current usage of small-scale loans by people with disabilities, strengthening relationships between disability organisations and microfinance institutions, and more rigorous enforcement of the existing Federal disability legislation in Uganda.